Diversity of the Adult Frogs (Amphibia: Anura) in Prince of Songkla University, Pattani Campus, Thailand - Sangrueng, Lattapon; Buatip, Somsak; Petchsupa, Nirattisai; Srichairat, Nattawut (Naresuan University Journal: Science and Technology (NUJST), 2021)
An investigation of adult frog diversity in Prince of Songkla University, Pattani Campus, Pattani Province of Thailand was carried out during March 2018 – February 2019 to provide the species checklist, habitats, relative abundance, Shannon–Wiener’s diversity, evenness indices, conservation status and to construct an area identification key to adult frog species and diagnosis morphological description. The surveys were conducted approximately 3-4 days each month. Five families, 8 genera and 11 species: Bufonidae (1 species), Dicroglossidae (3 species), Microhylidae (5 species), Ranidae (1 species), and Rhacophoridae (1 species) were found in this research. They were found in temporary ponds except Hylarana erythraea found in freshwater ponds only. The analysis of relative abundance revealed that Duttaphrynus melanostictus and Fejervarya limnocharis showed the highest value (78.38%) whereas Micryletta inornata showed the lowest value (2.70%). Additionally, the results of the Shannon–Wiener’s diversity and evenness indices were 2.01 and 0.68, respectively. In this study, the conservation status of most species was the least concern, except for Polypedates discantus was not evaluated. Moreover, the area identification key to adult frog species and diagnosis morphological description were provided. Keywords: Adult frogs, Anura, Diversity, Pattani Campus, Prince of Songkla University